The stigmatisation of source isolation: a literature review. (December 2019) - Gammon, John; Hunt, Julian; Musselwhite, Charles
Background: Isolation precautions in patients with multi-drug-resistant bacteria and other communicable infectious agents can be associated with adverse effects. Patients' perspectives of isolation suggest that the imposed environment and procedures create barriers to their physical, social and emotional needs. Aims: The purpose of this paper is to review the literature to uncover any reliable evidence supporting the assertion that stigma is a significant characteristic of the experience of source isolation in healthcare settings. Methods: The methodological framework of Arksey and O'Malley was applied to this review. A total of 14 papers identified from 189 abstracts screened were included in the review. Results: The research reviewed suggests a clear association between stigmatisation and isolation in which stigma does have a direct negative effect on patients placed in hospital isolation. None of the studies found evidence to the contrary. Conclusions: The implications of this literature review for policy-makers and healthcare professionals suggest that when isolation or other forms of constraint are implemented and in use, patients must be provided with strengthened forms of support, including social and emotional support, and given access to healthcare of optimal quality to prevent the associated adverse effects of isolation as much as possible.